(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The article analyzes in detail investments in the education system, goals and measures aimed at developing the education system, the international program for assessing the educational achievements of students PIRLS, TIMSS, PISA and TALIS, the integration of the republic’s education system into the world education system. The article also provides a framework of key competencies, professionally important qualities of leaders of the preschool and school education system, the specifics of management activities, personal characteristics of an education director, a model of a modern leader, and a professional profile of an education director.